PENGARUH FASILITAS BENGKEL TERHADAP MINAT BELAJAR DAN PENGUASAAN KOMPETENSI KEJURUAN SISWA SMK TEKNIK PEMESINAN DI PROVINSI GORONTALO: The Influence Of Workshop Facilities On Learning Interest And Mastery Of Vocational Competencies Of Machinery Engineering Vocational School Students In Gorontalo Province - Hendra Uloli; Esta Larosa; I Wayan Rupawan (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
Write the abstract in English here. If articles in English, abstract in Indonesia language do not need to be included. Writing abbreviations and mathematical formulas in the abstract needs to be avoided. The abstract consists of summary of the research objectives, approaches or methods used, important results and conclusions. This study aims to determine the effect of workshop facilities on students' learning interest and mastery of vocational competencies in the Mechanical Engineering expertise program at SMK Gorontalo Province. The background of this study is based on the importance of the role of workshop facilities in increasing students' learning interest which emphasizes mastery of competencies. The research method used is quantitative research, using path analysis to determine the relationship between two or more variables expressed by the magnitude of the correlation coefficient and statistical significance. This study discusses three variables consisting of one independent variable, namely the effect of workshop facilities (X) two dependent variables, namely learning interest (Y1) and (Y2) mastery of vocational competencies. The research sample consisted of XII students majoring in Mechanical Engineering at several state vocational schools in Gorontalo Province. Data were collected through questionnaires, The results of the analysis showed that there was a positive and significant influence between 1. workshop facilities on learning interest of 38.4 while 62.6% was influenced by other factors that were not examined, 2. Workshop facilities on competency mastery had a significant effect of 46.9% while 53.1% was influenced by other factors that were not examined. 3. Interest in learning towards competency mastery has a significant effect of 55% while 45% is influenced by other factors not studied. 4. Workshop facilities through interest in learning towards competency mastery have a significant effect of 64.20% while 35.8% is influenced by factors not studied.